Ischemic and injured bowel evaluation by Fluorescence imaging - Nowak, Kai; Şandra-Petrescu, Flavius Ionuţ; Post, Stefan; Horisberger, Karoline (Colorectal disease, 2015)
Abstract Aim Although fluorescence has been proposed for estimation of bowel perfusion decades ago it is still not widely used. In emergency situations like mesenteric ischemia, fluorescence might give objective criteria to evaluate the perfusion and guide the decisions of surgeons. Method The use of near?inrafrared angiography by PinPoint (Novadaq) in a serial of four emergency situations of acute mesenteric ischemia has been evaluated in a university hospital setting. Results The use of the near?infrared tool is in emergency situations easy to handle and little time?consuming. The angiography showed clearly the perfusion in regions that were not estimated as recoverable by the surgeons. In one of the cases a significant amount of bowel could be spared by use of the system. Conclusion Although the assessment of the perfusion with the applied system is comprehensible, it would be desirable to evaluate a threshold level in order to further objectify it. While the surgeons who used the tool were subjectively assured by the expressiveness it would need a randomized and maybe experimental setting to evaluate objectively the amount of spared bowel length.